Mixed Training Program: Helping Seesaw to Develop Blended Learning at the Community Learning Center - Sari, Ruhyat Wulan; Khaerudin, Khaerudin; Kusumawardani, Dwi (LPPM Undiksha, 2022)
All tutors work from home and only one day a week from the office, so an innovative learning approach is required. This study aims to produce a blended training program using seesaw to develop a blended learning design. The type of research used is research and development with a system approach that refers to the ADDIE and PEDATI models. Methods of collecting data with questionnaires, interviews, observations, documentation studies and tests. The feasibility test consists of expert review, one to one trial and small group trial. Based on the results of the feasibility test in expert review phase, this training program needs improvements in learning design aspects such as the learning models and methods used, discussion materials, task materials, and prerequisite competencies. Improvements to material aspects such as complete non examples and materials are arranged from the easiest to the most difficult. Improvements in the aspects of learning media is using color in slide background. The results of the one to one phase of feasibility test is improvement regarding time to achieve competency prerequisites, it is necessary to add reference sources in the form of links or qr codes, and it’s better to provide non video tutorials when on using the seesaw application. The results of the small group feasibility test still need improvement, using pdf format in presentation slide. The results of the effective test showed that there was an increase in cognitive domain learning outcomes between the pretest and posttest so that the trainees were able to develop blended learning designs. The N-Gain score of the increase is 0.62 (61.70%) with a fairly effective category.